ESTIMATION OF QUALITY APPROBATION OF ORE OF HANQAVAN MOLYBDENUM DEPOSITS (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In the article the imposing of present slit of column boring and heavy type mountain produces are considered on the example of Hanqavan molybdenum deposit. By the exploration it is established that systematic lowering of content of molybdenum in the trials of core at its low percentage exit and raising it by furrowed trials. It is explained with eroding and bearing molybdenum, with the washing liquid, at the first case and at the second case with electoral painting of molybdenum in the trial, at the repelling of fissure. Different meaning inaccuracies of selection trial by size are approximately the same and by using the mountain boring system of prospecting they are mutual liquidated. The receipt results of the investigation allow to apply the mountain boring system of prospecting in the copper-molybdenum deposit with the sprinkle types instrument.
Keywords: Hanqavan molybdenum deposit; mountain boring system; column boring system